2016
DOI: 10.14814/phy2.12865
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic perconditioning attenuates ischemia/reperfusion-induced downregulation of AQP2 in rat kidney

Abstract: Renal ischemia/reperfusion (I/R) can lead to impaired urine concentration ability and increased fractional excretion of sodium (FeNa). Local ischemic preconditioning improves renal water and sodium handling after I/R injury. Here, we investigate whether remote ischemic perconditioning (rIPeC) prevents dysregulation of renal water and salt handling in response to I/R injury and mechanisms that may be involved. Rats were subjected to right nephrectomy and randomized into a sham group or an I/R group. In the I/R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Urine osmolality in the I-R group significantly declined compared to the control group due to impaired urinary concentrating ability. Unsuitable regulation of the AQPs and Na + transporter proteins in renal tubules is responsible for changes in sodium and water regulation under the influence of ischemia-reperfusion injury [23]. Urine osmolarity in the NG group was not significantly different from that of the I-R group.…”
Section: Discussionmentioning
confidence: 84%
“…Urine osmolality in the I-R group significantly declined compared to the control group due to impaired urinary concentrating ability. Unsuitable regulation of the AQPs and Na + transporter proteins in renal tubules is responsible for changes in sodium and water regulation under the influence of ischemia-reperfusion injury [23]. Urine osmolarity in the NG group was not significantly different from that of the I-R group.…”
Section: Discussionmentioning
confidence: 84%
“…Inappropriate regulation of the AQPs and Na + transporter proteins in renal tubules and decreasing the expression of Na + /K + -ATPase in the thick descending limb of the external medulla that causing changes in sodium and water regulation under the influence of I-R injury. 19 In the hydralazine-treated rats, urinary osmolality was significantly more than that of the I-R rats. Previous studies have shown that hydralazine reduces urinary volume due to water and sodium retention.…”
Section: Discussionmentioning
confidence: 84%
“…30 In addition, I-R causes brush border destruction with reduced reabsorption of sodium by proximal tubules, impaired expression of tubular sodium transporters and unsuitable regulation of Na + /K + -ATPase expression in the basolateral membranes. 19,30 In the I-R injury lead to direct injury of cells responsible for the secretion of potassium in the distal tubules and collecting ducts. 31 Post-treatment of hydralazine in the I-R rats reduced urinary excretion of sodium compared to the I-R rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AQP2 was first discovered in the early 1990s, it is a member of the aquaporin family (16). AQP2 mainly exists in the cytoplasm of principal cell of renal collecting duct and the cell membrane towards the luminal side, which can increase the ability of water reabsorption and urine concentration (17). It was indicated in the results of this study that ALB level in children with hydronephrosis was significantly lower than that in normal children and it was significantly increased after treatment (P<0.05).…”
Section: Discussionmentioning
confidence: 99%